Optimal cold sink temperature for thermoelectric dehumidifiers - Kim, Joonoh; Park, Keunhwan; Lee, Duck-Gyu; Chang, Young Soo; Kim, Ho-Young (Journal of mechanical science and technology, 2018)
We propose an optimal cold sink temperature for thermoelectric dehumidifiers based on theoretical and experimental investigations. We show that the optimal condition is such that the latent heat absorption rate per unit power supplied to the dehumidifier is maximized. In consideration of the cooling ability of Peltier pellet and the heat exchange characteristics of the cold sink, we estimate the condensation rate as a function of the cold sink temperature. The theoretical predictions are compared with the results of experiments by using a prototype dehumidifier. We emphasize that the cold sink temperature is a critical parameter that determines the performance of dehumidification. Our study may provide an important insight to the thermoelectric dehumidification system and to designing a cold sink for thermoelectric dehumidifiers with improved energy efficiency.